2020
DOI: 10.1039/d0ra02435j
|View full text |Cite
|
Sign up to set email alerts
|

A compatibility study on the glycosylation of 4,4′-dihydroxyazobenzene

Abstract: The glycosylation of 4,4′-dihydroxyazobenzene was investigated to identify suitable conditions providing access to valuable photoswitchable glycoconjugates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 53 publications
0
14
1
Order By: Relevance
“…Azobenzene‐modified glycoconjugates have been widely used in the field of biochemistry, [ 262 ] and they also show potential utility in studying the interactions between carbohydrates and proteins. [ 263 ] Carbohydrate derivatives (for example, pyranose derivatives) are building blocks that have a good biocompatibility and a high degree of functional and structural diversity. Therefore, the presence of sugar units in the macrocycle makes it possible to regulate the physical and chemical properties of the entire ring system.…”
Section: Main Specific Applications Of Azobenzenementioning
confidence: 99%
See 2 more Smart Citations
“…Azobenzene‐modified glycoconjugates have been widely used in the field of biochemistry, [ 262 ] and they also show potential utility in studying the interactions between carbohydrates and proteins. [ 263 ] Carbohydrate derivatives (for example, pyranose derivatives) are building blocks that have a good biocompatibility and a high degree of functional and structural diversity. Therefore, the presence of sugar units in the macrocycle makes it possible to regulate the physical and chemical properties of the entire ring system.…”
Section: Main Specific Applications Of Azobenzenementioning
confidence: 99%
“…Therefore, the presence of sugar units in the macrocycle makes it possible to regulate the physical and chemical properties of the entire ring system. [ 264 ] The glycosylation of azobenzene derivatives (e.g., 4,4′‐dihydroxyazobenzene (DHAB) [ 263 ] ) is usually the first critical step to consider when constructing a photoresponsive macromolecular system. [ 265 ] DHAB is not a very active glycosyl acceptor because tautomerism between the quinone and phenol form leads to a decrease in nucleophilicity of phenolic hydroxy groups.…”
Section: Main Specific Applications Of Azobenzenementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we have recently investigated this reaction in detail and concluded that the scope of glycosyl donors and activation methods is very limited. [13] Likewise, the use of the Mitsunobu reaction for the conjugation of DHAB to the anomeric center or primary positions of glycosides was highly substrate-dependent and often led to low to moderate yields. [13] In view of the contrasting results obtained with the aforementioned methods, we sought for a reliable conjugation reaction effective on a wide scope of substrates, also including more sophisticated azoswitches such as ortho-substituted azobenzenes [15] and diazocine, an orthoethylene bridged azobenzene.…”
Section: Introductionmentioning
confidence: 99%
“…We investigated recently this reaction in detail and concluded that the scope of glycosyl donors and activation methods is very limited. 12 As well, the use of Mitsunobu reaction for the conjugation of DHAB to the anomeric centre or primary positions of glycosides was highly substrate-dependent and often led to low to moderate yields. 13b In view of the contrasted results obtained with the aforementioned methods, we sought for a reliable conjugation reaction effective on a wide scope of substrates, also including more sophisticated azoswitches such as ortho-substituted azobenzenes 14 and diazocine, an ortho-ethylene bridged azobenzene.…”
Section: Introductionmentioning
confidence: 99%